A high-strength flame-retardant wall material and its preparation process
By combining modified bentonite with aluminum sulfate, a cross-linked copolymer with a network structure is generated, which solves the problems of insufficient strength and cracking of existing wall materials, and achieves high strength, impermeability, flame retardancy and heat insulation, thus extending the service life.
Patent Information
- Application Number
- CN202511194679.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2025-08-26
- Publication Date
- 2025-11-14
- Estimated Expiration
- 2045-08-26
AI Technical Summary
Existing wall materials have shortcomings in terms of strength, crack resistance, and thermal insulation performance, which limits their widespread application.
Modified bentonite is combined with other raw materials, and the surface of bentonite is modified with a silane coupling agent. Under the action of an initiator and a crosslinking agent, an N-vinylpyrrolidone/vinyl acetate crosslinking copolymer is generated to form a network structure, which improves the dispersibility and adhesion of bentonite. It is also complexed with aluminum sulfate to enhance the stability of the material.
It improves the compressive strength, impermeability, and flame retardancy of wall materials, while reducing the risk of cracking and extending their service life.
Abstract
Description
Technical Field
[0001] This invention belongs to the field of wall material technology, specifically, it is a high-strength flame-retardant wall material and its preparation process. Background Technology
[0002] With the improvement of my country's economic level and the continuous advancement of urbanization, people's living conditions are improving day by day, and their requirements for housing comfort are also increasing. Various wall materials are constantly being introduced, such as hollow bricks, calcium silicate composite wall panels, and autoclaved blocks, but each has its own shortcomings. Hollow bricks, due to their porous structure, reduce their weight, but their strength and thermal insulation performance are affected, making it difficult to promote their widespread use. Calcium silicate composite wall panels have defects such as large drying shrinkage and low compressive strength, which limit their development.
[0003] Autoclaved aerated concrete (AAC) blocks are made primarily from coal slag and fly ash. They are widely used, inexpensive, and offer advantages such as lightweight and thermal insulation. However, they also face some quality issues, such as deformation and cracking, which severely impact the lifespan and performance of buildings, and significantly reduce the thermal insulation and waterproofing properties of walls. The alternating hot and cold weather in northern regions causes the expansion and contraction of wall materials, leading to wall cracking and hindering the development of AAC blocks.
[0004] The patent, titled "An Environmentally Friendly Wall Brick and Its Processing Method," with patent number "CN202211682352.0," incorporates graphene oxide aerogel into raw materials such as fly ash. This not only ensures good adhesion to the matrix and uniform distribution, preventing cracks, but also strengthens and toughens the wall brick. Zeolite powder is fixed in the graphene oxide aerogel through hydrothermal treatment followed by freeze-drying, providing skeletal support and preventing breakage. This also allows the graphene oxide aerogel to be evenly dispersed in the matrix. The porous structure of the graphene oxide aerogel improves the material's thermal insulation effect. However, the complex process limits its large-scale production and application. Summary of the Invention
[0005] In order to solve the problems existing in the prior art, the present invention proposes a high-strength flame-retardant wall material and its preparation process, so as to achieve the invention objectives of improving the strength of wall materials, preventing cracking, and extending service life.
[0006] One of the objectives of this invention is to provide a high-strength flame-retardant wall material, wherein the raw materials of the high-strength flame-retardant wall material, by weight, include the following components: 60-70 parts fly ash, 16-20 parts cement, 20-25 parts carbide slag, 9-12 parts modified bentonite, 5-7 parts lime, 4-6 parts calcium phosphate, 4-6 parts aluminum silicate, 2-3 parts aluminum sulfate, and 35-40 parts water.
[0007] Preferably, the modified bentonite is prepared by:
[0008] S1. Add the silane coupling agent to the ethanol solution and ultrasonically disperse for 10-20 min. Adjust the pH to 4-5, add bentonite and ultrasonically disperse for 30-40 min. React at 60-70℃ for 4-6 h. After centrifugation, washing with anhydrous ethanol and drying, modify the surface of the bentonite with unsaturated double bond structure to obtain pretreated bentonite.
[0009] S2. Add N-vinylpyrrolidone, vinyl acetate, pretreated bentonite, and emulsifier to deionized water and stir for 20-30 min. Then add initiator and crosslinking agent and continue stirring for 10-15 min. Heat to 60-70℃ and stir under nitrogen protection for 5-6 h. After the reaction is complete, cool, filter, wash with anhydrous ethanol, and dry to obtain modified bentonite.
[0010] Preferably, the bentonite in S1 has a particle size of 1–5 μm.
[0011] Preferably, the silane coupling agent in S1 is KH570, and the amount added is 5-8% of the mass of bentonite.
[0012] Preferably, the volume ratio of ethanol to water in the ethanol solution in S1 is 2 to 3:1.
[0013] Preferably, the drying temperature in S1 is 60-70°C and the drying time is 12-18 hours.
[0014] Preferably, the mass ratio of N-vinylpyrrolidone, vinyl acetate, pretreated bentonite, emulsifier, and deionized water in S2 is 2-4:6-10:14-16:0.2-0.3:70-80.
[0015] Preferably, the emulsifier in S2 is one or more of alkylphenol polyoxyethylene ether, Tween 80, and isooctanol polyoxyethylene ether.
[0016] Preferably, the initiator in S2 is potassium persulfate, and the amount added is 1 to 1.8% of the mass of vinyl acetate; the crosslinking agent is N,N'-methylenebisacrylamide, and the amount added is 1.5 to 2% of the mass of N-vinylpyrrolidone.
[0017] Preferably, the stirring rate in S2 is 500-600 r / min.
[0018] Preferably, the drying temperature in step S2 is 60–70°C, and the drying time is 12–18 hours.
[0019] Bentonite acts as a filler and binder in wall materials, possessing strong adhesion and water absorption. It can improve the compactness of the internal structure of the material to a certain extent, enhancing the wall's impermeability and preventing shrinkage and deformation caused by excessively rapid drying. However, in practical applications, the following drawbacks exist: Because bentonite is a powdery small particle, dispersion is difficult during addition, leading to uneven wall material distribution and a risk of cracking, thus reducing compressive strength; bentonite's excessive water absorption, expanding dozens of times in volume after absorbing water, can cause rapid expansion of the wall material, reducing compressive strength and even causing cracking; and after long-term use, the bonding force between bentonite and fly ash, cement, etc., becomes insufficient, resulting in reduced compressive strength.
[0020] Pretreated bentonite was obtained by modifying the surface of bentonite with unsaturated double bonds using a silane coupling agent. Then, under the action of an initiator and a crosslinking agent, it underwent free radical polymerization and crosslinking, generating an N-vinylpyrrolidone / vinyl acetate crosslinked copolymer on the surface of the pretreated bentonite, forming a network structure. This crosslinked copolymer combines the properties of both crosslinked polyvinylpyrrolidone and vinyl acetate. Crosslinked polyvinylpyrrolidone is insoluble in water but possesses swelling and complexing ion capabilities; vinyl acetate exhibits hydrophobicity, adhesion, and flexibility, while simultaneously inhibiting the swelling of crosslinked polyvinylpyrrolidone. Therefore, the N-vinylpyrrolidone / vinyl acetate crosslinked copolymer possesses amphiphilicity and better structural stability.
[0021] The N-vinylpyrrolidone / vinyl acetate cross-linked copolymer with a network structure not only improves the dispersibility of bentonite, but also effectively inhibits the volume expansion of bentonite after water absorption. Its flexibility also reduces stress concentration caused by the volume expansion of bentonite after water absorption, acting as a buffer and significantly reducing the risk of wall cracking after moisture exposure. The bentonite and the N-vinylpyrrolidone / vinyl acetate cross-linked copolymer are chemically bonded, preventing delamination and extending service life.
[0022] The second objective of this invention is to provide a preparation process for a high-strength flame-retardant wall material. The preparation process is as follows: fly ash, cement, carbide slag, modified bentonite, lime, calcium phosphate, aluminum silicate, and aluminum sulfate are mixed and stirred evenly, then water is added and stirred evenly again. After digestion treatment, the mixture is added to a mold and pressed into shape. The shaped sample is left to dry statically, then subjected to autoclaving and curing, and stacked for 28 days to obtain the high-strength flame-retardant wall material.
[0023] Preferably, the digestion treatment is carried out at a temperature of 20–30°C for 1.5–3 hours.
[0024] Preferably, the pressing pressure is 18-22 MPa.
[0025] Preferably, the autoclaving temperature is 180–200°C and the time is 10–12 hours.
[0026] Adding aluminum sulfate to the raw materials causes aluminum sulfate to dissolve in water and generate aluminum ions. The pyrrolidone structure in the N-vinylpyrrolidone-vinyl acetate cross-linked copolymer on the surface of the modified bentonite complexes with the aluminum ions, making the internal structure of the resulting wall material more stable and further improving its compressive strength.
[0027] By adopting the above technical solution, the technical effect achieved by the present invention is as follows:
[0028] 1. The high-strength flame-retardant wall material prepared by this invention not only has high strength and good seepage prevention effect, but also has excellent flame-retardant and thermal insulation properties, and has a wider range of application and development space.
[0029] 2. This invention modifies bentonite, which improves both the dispersibility of bentonite and its bonding ability with the matrix, resulting in a denser structure and higher compressive strength of the wall material.
[0030] 3. The high-strength flame-retardant wall material prepared by this invention has a compressive strength of 26.4–29.2 MPa and a flexural strength of 7.8–8.5 MPa (measured according to GB / T 2542-2012).
[0031] 4. The high-strength flame-retardant wall material prepared by this invention has a water absorption rate of 12.7-13.3% (determined according to GB / T 4111-2013) and a drying shrinkage value of 0.35-0.37 mm / m (determined according to JC / T 239-2014).
[0032] 5. The high-strength flame-retardant wall material prepared by this invention has a thermal conductivity of 0.128~0.141W / m·K (measured according to YB / T 4130-2005), a limiting oxygen index greater than 30%, and good thermal insulation and flame-retardant effects.
[0033] 6. The high-strength flame-retardant wall material prepared by this invention has a softening coefficient greater than 0.87 (determined according to GB / T 11968-2020), meeting the water resistance requirements and suitable for humid environments; the carbonization coefficient is 1.03~1.08 (determined according to JC / T239-2014), indicating good durability; after 30 freeze-thaw cycles (-15℃~20℃), the mass loss rate is 0.53~0.62%, and the strength loss rate is 5.64~6.01% (determined according to GB / T 11968-2020). Detailed Implementation
[0034] To further illustrate the technical means and effects of the present invention in achieving the intended purpose, the following detailed description of the specific implementation methods, structures, features and effects of the present invention, in conjunction with preferred embodiments, is provided below.
[0035] Example 1: A high-strength flame-retardant wall material and its preparation process
[0036] A high-strength flame-retardant wall material, wherein the raw materials of the high-strength flame-retardant wall material include the following components by weight: 65 parts fly ash, 18 parts cement, 22 parts carbide slag, 11 parts modified bentonite, 6 parts lime, 5 parts calcium phosphate, 5 parts aluminum silicate, 3 parts aluminum sulfate, and 38 parts water.
[0037] The method for preparing the modified bentonite is as follows:
[0038] S1. Add the silane coupling agent to the ethanol solution and ultrasonically disperse for 15 min. Adjust the pH to 4.5, add bentonite and ultrasonically disperse for 35 min. React at 65℃ for 5 h. After centrifugation, washing with anhydrous ethanol and drying, modify the surface of the bentonite with unsaturated double bond structure to obtain pretreated bentonite.
[0039] S2. Add N-vinylpyrrolidone, vinyl acetate, pretreated bentonite, and emulsifier to deionized water and stir for 25 min. Then add initiator and crosslinking agent and continue stirring for 12 min. Heat to 65℃ and stir under nitrogen protection for 5.5 h. After the reaction is complete, cool, filter, wash with anhydrous ethanol, and dry to obtain modified bentonite.
[0040] The bentonite in S1 has a particle size of 2 μm.
[0041] The silane coupling agent in S1 is KH570, and the amount added is 6.5% of the mass of bentonite.
[0042] The volume ratio of ethanol to water in the ethanol solution in S1 is 2:1.
[0043] The drying temperature in S1 is 65°C, and the drying time is 16 hours.
[0044] The mass ratio of N-vinylpyrrolidone, vinyl acetate, pretreated bentonite, emulsifier, and deionized water in S2 is 3:8:15:0.25:75.
[0045] The emulsifier in S2 is alkylphenol polyoxyethylene ether.
[0046] The initiator in S2 is potassium persulfate, and the amount added is 1.5% of the mass of vinyl acetate; the crosslinking agent is N,N'-methylenebisacrylamide, and the amount added is 1.7% of the mass of N-vinylpyrrolidone.
[0047] The stirring rate in S2 is 550 r / min.
[0048] The drying temperature in S2 is 65°C, and the drying time is 16 hours.
[0049] A preparation process for a high-strength flame-retardant wall material is disclosed. The preparation process is as follows: fly ash, cement, carbide slag, modified bentonite, lime, calcium phosphate, aluminum silicate, and aluminum sulfate are mixed and stirred evenly. Water is then added and stirred evenly again. After digestion treatment, the mixture is added to a mold and pressed into shape. The shaped sample is left to dry for 7 hours, then subjected to autoclaving and curing, and stacked for 28 days to obtain the high-strength flame-retardant wall material.
[0050] The digestion process was carried out at a temperature of 25°C for 2.5 hours.
[0051] The pressure for compression molding is 20 MPa.
[0052] The autoclaving temperature was 190℃ and the time was 11 hours.
[0053] Example 2: A high-strength flame-retardant wall material and its preparation process
[0054] A high-strength flame-retardant wall material, wherein the raw materials of the high-strength flame-retardant wall material include the following components by weight: 60 parts fly ash, 16 parts cement, 20 parts carbide slag, 9 parts modified bentonite, 5 parts lime, 4 parts calcium phosphate, 6 parts aluminum silicate, 2 parts aluminum sulfate, and 35 parts water.
[0055] The modified bentonite is prepared by:
[0056] S1. Add the silane coupling agent to the ethanol solution and ultrasonically disperse for 10 min. Adjust the pH to 4, add bentonite and ultrasonically disperse for 30 min. React at 60℃ for 4 h. After centrifugation, washing with anhydrous ethanol and drying, modify the surface of the bentonite with unsaturated double bond structure to obtain pretreated bentonite.
[0057] S2. Add N-vinylpyrrolidone, vinyl acetate, pretreated bentonite, and emulsifier to deionized water and stir for 20 min. Then add initiator and crosslinking agent and continue stirring for 10 min. Heat to 60℃ and stir under nitrogen protection for 5 h. After the reaction is complete, cool, filter, wash with anhydrous ethanol, and dry to obtain modified bentonite.
[0058] The bentonite in S1 has a particle size of 1 μm.
[0059] The silane coupling agent in S1 is KH570, and the amount added is 5% of the mass of bentonite.
[0060] The volume ratio of ethanol to water in the ethanol solution in S1 is 2:1.
[0061] The drying temperature in S1 is 60°C, and the drying time is 18 hours.
[0062] The mass ratio of N-vinylpyrrolidone, vinyl acetate, pretreated bentonite, emulsifier, and deionized water in S2 is 2:6:14:0.2:70.
[0063] The emulsifier in S2 is alkylphenol polyoxyethylene ether.
[0064] The initiator in S2 is potassium persulfate, and the amount added is 1% of the mass of vinyl acetate; the crosslinking agent is N,N'-methylenebisacrylamide, and the amount added is 1.5% of the mass of N-vinylpyrrolidone.
[0065] The stirring rate in S2 is 500 r / min.
[0066] The drying temperature in S2 is 60°C, and the drying time is 18 hours.
[0067] A preparation process for a high-strength flame-retardant wall material is disclosed. The preparation process is as follows: fly ash, cement, carbide slag, modified bentonite, lime, calcium phosphate, aluminum silicate, and aluminum sulfate are mixed and stirred evenly. Water is then added and stirred evenly again. After digestion treatment, the mixture is added to a mold and pressed into shape. The shaped sample is left to stand and dry for 6 hours, then subjected to autoclaving and curing, and stacked for 28 days to obtain the high-strength flame-retardant wall material.
[0068] The digestion process was carried out at a temperature of 20°C for 3 hours.
[0069] The pressing pressure is 18 MPa.
[0070] The autoclaving temperature is 180℃ and the time is 12 hours.
[0071] Example 3: A high-strength flame-retardant wall material and its preparation process
[0072] A high-strength flame-retardant wall material, wherein the raw materials of the high-strength flame-retardant wall material include the following components by weight: 70 parts fly ash, 20 parts cement, 25 parts carbide slag, 12 parts modified bentonite, 7 parts lime, 6 parts calcium phosphate, 4 parts aluminum silicate, 2.5 parts aluminum sulfate, and 40 parts water.
[0073] The modified bentonite is prepared by:
[0074] S1. Add the silane coupling agent to the ethanol solution and ultrasonically disperse for 20 min. Adjust the pH to 5, add bentonite and ultrasonically disperse for 40 min. React at 70℃ for 6 h. After centrifugation, washing with anhydrous ethanol and drying, modify the surface of the bentonite with unsaturated double bond structure to obtain pretreated bentonite.
[0075] S2. Add N-vinylpyrrolidone, vinyl acetate, pretreated bentonite, and emulsifier to deionized water and stir for 30 min. Then add initiator and crosslinking agent and continue stirring for 15 min. Heat to 70℃ and stir under nitrogen protection for 6 h. After the reaction is complete, cool, filter, wash with anhydrous ethanol, and dry to obtain modified bentonite.
[0076] The bentonite in S1 has a particle size of 5 μm.
[0077] The silane coupling agent in S1 is KH570, and the amount added is 8% of the mass of bentonite.
[0078] The volume ratio of ethanol to water in the ethanol solution in S1 is 3:1.
[0079] The drying temperature in S1 is 70°C, and the drying time is 12 hours.
[0080] The mass ratio of N-vinylpyrrolidone, vinyl acetate, pretreated bentonite, emulsifier, and deionized water in S2 is 4:10:16:0.3:80.
[0081] The emulsifier in S2 is alkylphenol polyoxyethylene ether.
[0082] The initiator in S2 is potassium persulfate, and the amount added is 1.8% of the mass of vinyl acetate; the crosslinking agent is N,N'-methylenebisacrylamide, and the amount added is 2% of the mass of N-vinylpyrrolidone.
[0083] The stirring rate in S2 is 600 r / min.
[0084] The drying temperature in S2 is 70°C, and the drying time is 12 hours.
[0085] A preparation process for a high-strength flame-retardant wall material is disclosed. The preparation process is as follows: fly ash, cement, carbide slag, modified bentonite, lime, calcium phosphate, aluminum silicate, and aluminum sulfate are mixed and stirred evenly. Water is then added and stirred evenly again. After digestion treatment, the mixture is added to a mold and pressed into shape. The shaped sample is left to dry for 8 hours, then subjected to autoclaving and curing, and stacked for 28 days to obtain the high-strength flame-retardant wall material.
[0086] The digestion process was carried out at a temperature of 30°C for 1.5 hours.
[0087] The pressure for compression molding is 22 MPa.
[0088] The autoclaving temperature is 200℃ and the time is 10 hours.
[0089] Comparative Example 1: A representative example 1 was selected, in which the modified bentonite was replaced with an equal amount of bentonite, and all other aspects were the same as in Example 1, serving as Comparative Example 1.
[0090] Comparative Example 2: A representative example, Example 1, was selected. The crosslinking agent in S2 was removed, and the rest was the same as Example 1. This was used as Comparative Example 2.
[0091] Comparative Example 3: A representative Example 1 was selected, step S1 was removed, and the rest was the same as Example 1, which was used as Comparative Example 3.
[0092] Comparative Example 4: A representative example, Example 1, was selected, but aluminum sulfate was removed from the raw materials. All other aspects were the same as in Example 1. This example is used as Comparative Example 4.
[0093] The wall materials prepared in Examples 1-3 and Comparative Examples 1-3 were subjected to performance testing, as detailed in Tables 1 and 2.
[0094] Table 1
[0095] Testing items Example 1 Example 2 Example 3 Compressive strength (MPa) 28.2 26.4 27.3 Flexural strength (MPa) 8.5 7.8 8.1 Water absorption rate (%) 12.7 13.3 13.1 Drying shrinkage value (mm / m) 0.35 0.37 0.36 Thermal conductivity (W / m·K) 0.128 0.141 0.132 Limiting oxygen index (%) 31.3 30.8 31.1 Softening coefficient 0.9 0.88 0.89 Carbonization coefficient 1.08 1.03 1.06 Mass loss rate after 30 freeze-thaw cycles (%) 0.53 0.62 0.56 Strength loss rate after 30 freeze-thaw cycles (%) 5.64 6.01 5.79
[0096] Table 2
[0097] Testing items Example 1 Comparative Example 1 Comparative Example 2 Comparative Example 3 Comparative Example 4 Compressive strength (MPa) 28.2 18.5 21.4 28 23.1 Flexural strength (MPa) 8.5 5.4 6.9 8.4 7.2 Water absorption rate (%) 12.7 14.1 13.8 13.3 12.9 Drying shrinkage value (mm / m) 0.35 0.47 0.43 0.41 0.39 Softening coefficient 0.9 0.8 0.81 0.9 0.86 Carbonization coefficient 1.08 0.95 0.98 1 1.03 Mass loss rate after 30 freeze-thaw cycles (%) 0.53 0.7 0.68 0.66 0.62 Strength loss rate after 30 freeze-thaw cycles (%) 5.64 9.1 8.75 8.26 7.95
[0098] As can be seen from Table 1, the wall material prepared by this invention not only has high strength, but also exhibits excellent performance in terms of water resistance, durability, frost resistance, flame retardancy, and thermal insulation.
[0099] Comparative Example 1 uses unmodified bentonite, which has poor dispersibility. Therefore, the overall strength of the wall material is reduced, but the water absorption is increased, the drying shrinkage is increased, and the risk of cracking is increased; all performance effects are reduced.
[0100] In Comparative Example 2, no crosslinking agent was added in step S2. The N-vinylpyrrolidone / vinyl acetate copolymer formed on the surface of the bentonite was water-soluble and easily detached during subsequent preparation processes and stirring with water, causing the exposed bentonite to agglomerate and affecting the performance of the wall material.
[0101] In Comparative Example 3, step S1 was removed. The bentonite and N-vinylpyrrolidone / vinyl acetate crosslinked copolymer are physically bonded. After long-term use, the bentonite and N-vinylpyrrolidone / vinyl acetate crosslinked copolymer are prone to delamination, resulting in slightly poorer durability.
[0102] In Comparative Example 4, the wall material without aluminum sulfate exhibited lower stability and strength compared to Example 1. This indicates that the pyrrolidone structure in the N-vinylpyrrolidone-vinyl acetate crosslinked copolymer on the surface of the modified bentonite complexes with aluminum ions, resulting in a more stable internal structure of the wall material and further improving its compressive strength.
[0103] Unless otherwise specified, all proportions and percentages mentioned in this invention are mass proportions and mass percentages; all raw materials are commercially available.
[0104] The above description is merely a preferred embodiment of the present invention and is not intended to limit the present invention in any way. Although the present invention has been disclosed above with reference to preferred embodiments, it is not intended to limit the present invention. Any person skilled in the art can make some modifications or alterations to the above-disclosed technical content to create equivalent embodiments without departing from the scope of the present invention. Any simple modifications, equivalent changes and alterations made to the above embodiments based on the technical essence of the present invention without departing from the scope of the present invention shall still fall within the scope of the present invention.
Claims
1. A high-strength flame-retardant wall material, characterized in that, The raw materials of the high-strength flame-retardant wall material, by weight, include the following components: 60-70 parts fly ash, 16-20 parts cement, 20-25 parts carbide slag, 9-12 parts modified bentonite, 5-7 parts lime, 4-6 parts calcium phosphate, 4-6 parts aluminum silicate, 2-3 parts aluminum sulfate, and 35-40 parts water. The modified bentonite is prepared by: S1. Add the silane coupling agent to the ethanol solution and ultrasonically disperse for 10-20 min. Adjust the pH to 4-5, add bentonite and ultrasonically disperse for 30-40 min. React at 60-70℃ for 4-6 h. After centrifugation, washing with anhydrous ethanol and drying, pretreated bentonite is obtained. S2. Add N-vinylpyrrolidone, vinyl acetate, pretreated bentonite, and emulsifier to deionized water and stir for 20-30 min. Then add initiator and crosslinking agent and continue stirring for 10-15 min. Heat to 60-70℃ and stir under nitrogen protection for 5-6 h. After the reaction is complete, cool, filter, wash with anhydrous ethanol, and dry to obtain modified bentonite.
2. The high-strength flame-retardant wall material according to claim 1, characterized in that, The bentonite in S1 has a particle size of 1–5 μm.
3. The high-strength flame-retardant wall material according to claim 1, characterized in that, The silane coupling agent in S1 is KH570, and the amount added is 5-8% of the mass of bentonite.
4. The high-strength flame-retardant wall material according to claim 1, characterized in that, The volume ratio of ethanol to water in the ethanol solution in S1 is 2 to 3:
1. The drying temperature in S1 is 60-70℃, and the drying time is 12-18h.
5. The high-strength flame-retardant wall material according to claim 1, characterized in that, The mass ratio of N-vinylpyrrolidone, vinyl acetate, pretreated bentonite, emulsifier, and deionized water in S2 is 2-4:6-10:14-16:0.2-0.3:70-80.
6. The high-strength flame-retardant wall material according to claim 1, characterized in that, The emulsifier in S2 is one or more of alkylphenol polyoxyethylene ether, Tween 80, and isooctyl alcohol polyoxyethylene ether; The initiator in S2 is potassium persulfate, and the amount added is 1 to 1.8% of the mass of vinyl acetate; the crosslinking agent is N,N'-methylenebisacrylamide, and the amount added is 1.5 to 2% of the mass of N-vinylpyrrolidone.
7. The high-strength flame-retardant wall material according to claim 1, characterized in that, The stirring rate in S2 is 500–600 r / min; The drying temperature in S2 is 60-70℃, and the drying time is 12-18h.
8. The preparation process of a high-strength flame-retardant wall material as described in any one of claims 1-7, characterized in that, The preparation process is as follows: fly ash, cement, carbide slag, modified bentonite, lime, calcium phosphate, aluminum silicate, and aluminum sulfate are mixed and stirred evenly, then water is added and stirred evenly again. After digestion treatment, the mixture is added into a mold and pressed into shape. The shaped sample is left to dry and then subjected to autoclaving and stacking for 28 days to obtain a high-strength flame-retardant wall material.
9. The preparation process of a high-strength flame-retardant wall material according to claim 8, characterized in that, The digestion process is carried out at a temperature of 20–30°C for 1.5–3 hours.
10. The preparation process of a high-strength flame-retardant wall material according to claim 8, characterized in that, The pressing pressure is 18-22 MPa; The autoclaving temperature is 180–200℃ and the time is 10–12 hours.
Citation Information
Patent Citations
Tobermorite type A-grade wall thermal insulation material based on synergy of carbide slag and silica fume and preparation method of tobermorite type A-grade wall thermal insulation material
CN113277794A
Environment-friendly wall brick and processing method thereof
CN116003059A